Modern Irish literature and the primitive sublime - McGarrity, Maria, 1970- author.
1 online resource.
Keywords: "Modern Irish Literature and the Primitive Sublime reveals the Primitive Sublime as an overlooked aspect of modern Irish literature as central to Ireland's artistic production and the wider global cultural production of Postcolonial literature. A concern for and anxiety about the primitive persists within modern Irish culture. The "otherness" within and beyond Ireland's borders offers writers, from the Celtic Revival through independence and partition to post 9/11, a seductive call through which to negotiate Irish identity. Ultimately, the disquieting awe of the primitive sublime is not simply a momentary recognition of Ireland's primitive indigenous history but a repeated rhetorical gesture that beckons a transcendent elation brought about by the recognition of the troubled, ritualistic and sacrificial Irish past to reveal a fundamental aspect of the capacity to negotiate identity, viewed through another but intimately reflective of the self, within the long emerging twentieth-century Irish nation"--